Die stad Jerigo en die boek Josua - Pienaar, Daniel N. (Journal for semitics, 1989)
Discoveries made during archaeological excavations are silent witnesses of a distant past. Often these witnesses are relevant for Biblical Studies, but almost as often the interpretation thereof is quite relative. The excavations at Jericho serve to illustrate this statement if the repeated re-assessments of the conclusions are kept in mind. When considering Jericho, it is appropriate to take into account the time of the conquest. At the time the excavations were undertaken by Warren, Sellin, Watzinger, Garstang and Kenyon, each one used the best methods available. Every expedition served as a corrective to the previous one. The results of the excavations at Jericho are very important, but also inspire modesty, as no one's conclusions can be regarded as final. In this paper the author concludes that Jericho was a relatively small settlement, and he requests that a new research program be launched in which the new insights of modem archaeology are implemented. New questions should be asked and possibly better answers will be given. It is suggested that the regional approach be applied. The motif for this new investigation should not be to question the historicity of the fall of Jericho, but to elucidate the conquest.